2019
DOI: 10.1101/724369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brown adipose expansion and remission of glycemic dysfunction in obese SM/J mice

Abstract: 52Disruption of glucose homeostasis increases the risk of type II diabetes, cardiovascular disease, stroke, 53 and cancer. We leverage a novel rodent model, the SM/J mouse, to understand glycemic control in 54 obesity. On a high fat diet, obese SM/J mice initially develop impaired glucose tolerance and elevated 55 fasting glucose. Strikingly, their glycemic dysfunction resolves by 30 weeks of age despite persistence of 56 obesity. A prominent phenotype is that they dramatically expand their brown adipose depot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 45 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…This is consistent with our previous work showing brown adipose tissue-dependent resolution of diabetes in high fat-fed SM/J mice [51]. Twenty-four of these hub genes contain small nucleotide variants between the LG/J and SM/J strains [57] ( Supplementary Table 6 ), which could be contributing to the gene-by-environmental differential expression patterns we observe.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…This is consistent with our previous work showing brown adipose tissue-dependent resolution of diabetes in high fat-fed SM/J mice [51]. Twenty-four of these hub genes contain small nucleotide variants between the LG/J and SM/J strains [57] ( Supplementary Table 6 ), which could be contributing to the gene-by-environmental differential expression patterns we observe.…”
Section: Resultssupporting
confidence: 92%
“…The brown cell division module shows remarkable clustering of the high fat-fed SM/J cohort, which is consistent with our result that enrichment of this term is driven by high fat-fed SM/J mice. Further, high fat-fed SM/J mice have the highest brown adipose to body weight ratios and our previous work showed that the brown adipose expansion observed in these mice is the result of hyperplasia [51]. Both pink peroxisome and red organic molecule processes show moderate diet-by-strain clustering.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations